2018
DOI: 10.7717/peerj.6037
|View full text |Cite
|
Sign up to set email alerts
|

Short-term interval aerobic exercise training does not improve memory functioning in relapsing-remitting multiple sclerosis—a randomized controlled trial

Abstract: BackgroundOnly few aerobic exercise intervention trials specifically targeting cognitive functioning have been performed in multiple sclerosis.Objective and MethodsThis randomized controlled trial with 34 patients in the intervention group (IG) (mean: 38.2 years (±9.6)) and 34 patients in the control group (CG) (mean: 39.6 years (±9.7)) aimed to determine the effects of aerobic exercise on cognition in relapsing-remitting multiple sclerosis (RRMS). The primary outcome was verbal learning assessed by the verbal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 53 publications
2
46
1
Order By: Relevance
“…Duration and the number of sessions could explain this reliability. The results of this study were inconsistent with that of Baquet et al [19].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Duration and the number of sessions could explain this reliability. The results of this study were inconsistent with that of Baquet et al [19].…”
Section: Discussioncontrasting
confidence: 99%
“…They found no significant effect of the treatments on the quality of life, frequency of fatigue, and depression, in patients with MS. The smaller sample size and lower exercise intensity could be the reasons behind the nonsignificant results in the study in question [19]. Besides, the pathophysiology of fatigue is not understood in MS patients; further studies are needed to explore the causes of fatigue and its descending trend following the training programs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Besides potential exercise regime independent benefits of exercise on cognition, HIIT applied in this study had a positive impact on physical fitness in pwMS. Against argued worries about potential losses of adherence linked to higher exercise intensities ( 30 ), this study showed high adherence rates by pwMS of several disability ranges. However, the setting remains an inpatient rehabilitation that is not comparable to outpatient settings.…”
Section: Discussionmentioning
confidence: 59%
“…The AERCONN trial [Exercise in Multiple Sclerosis: Effects on Cognitive Function and Brain Connectivity (NCT02005237)] is a rater-blinded, 1:1 randomized, controlled trial of aerobic exercise training over 3 months in MS compared to a waitlist control group. Details on trial design, intervention, and clinical outcomes have been published before (Baquet et al, 2018 ). Briefly, we recruited patients with relapsing-remitting MS (RRMS) according to the McDonald criteria 2010 (Polman et al, 2011 ) without relapse or disability progression during the last 3 months (January 2013–November 2015).…”
Section: Methodsmentioning
confidence: 99%